Edukasi Pencegahan Bullying dan Pentingnya Menjaga Kebersihan pada Siswa Sekolah Dasar di Desa Sukarame, Kecamatan Pacet, Kabupaten Bandung: Pengabdian - Sopyan Dwi; Syalma Alisa; Anny Hanifah; Fakhriansyah Adwitiya; Anita Fuji; Sani Rizqi; Sindy Eka; Ilham Tri; Resna Anggraeni; Farhan Fahrudin; Vera Martikasari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community Service Program (KKN) is one of the forms of student engagement with the community, aiming to provide real contributions in addressing local problems. The KKN activity carried out in Sukarame Village, Pacet District, Bandung Regency, focused on an educational program for elementary school students regarding bullying prevention and the importance of maintaining personal and environmental hygiene. The method used was an interactive educational approach through the delivery of materials, group discussions, educational games, and hands-on practice. The results of the activity showed an increase in students’ understanding of the negative impacts of bullying and greater awareness of the importance of cleanliness. This program is expected to foster positive attitudes in social interactions and build healthy habits from an early age.